Top 10 academic progress on traditional Chinese medicine in 2022 (Science of Traditional Chinese Medicine)
Background. To implement the spirit of the 20th National Congress of the Communist Party of China and the Opinions on Promoting the Inheritance, Innovation, and Development of Traditional Chinese Medicine (TCM), regularly summarize the research results of TCM, present the academic progress on TCM dynamically, and fully leverage the academic leadership of academic groups, the China Association of Chinese Medicine organized the selection of the top 10 academic progress on TCM in 2022. The selection process adhered to 4 orientations, eliminated any biases, highlighted the solutions to clinical problems, answered scientific questions, and led the industry’s development. It reflected an exploratory and forward-looking approach, emphasizing innovation and breakthroughs. The selection focused on new laws, new discoveries, new methods, new products, and new theories in the field of basic research and applied basic research in TCM. Through a process of dynamic collection, preliminary examination, review, and final judgment, the top 10 academic progress of TCM in 2022 were determined.